2022
DOI: 10.1101/2022.03.07.483380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thyroid hormone induces B cells abnormal differentiation via overexpression of B cell-activating factor

Abstract: Breakdown of tolerance and abnormal activation in B cells is an important mechanism in Graves’ disease (GD) pathogenesis. However, the mechanism by which B cells are abnormal differentiated and activated in GD remains elusive. Here, we show that elevated BAFF expression is positively correlated with serum thyroid hormone (TH) levels in GD patients and high TH levels can induce BAFF overexpression and lead to the abnormal differentiation of B cells in mice. This BAFF overexpression can be seen in many tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…This topic has recently been addressed and the results showed that high systemic concentrations of TT3 and T4 are associated with overexpression of BAFF and may have effects on B-cell differentiation [39]. In addition, it has been found that elevated concentrations of TT3 can induce polarization of M1 macrophages and this may lead to increased expression of BAFF [40].…”
Section: Discussionmentioning
confidence: 99%
“…This topic has recently been addressed and the results showed that high systemic concentrations of TT3 and T4 are associated with overexpression of BAFF and may have effects on B-cell differentiation [39]. In addition, it has been found that elevated concentrations of TT3 can induce polarization of M1 macrophages and this may lead to increased expression of BAFF [40].…”
Section: Discussionmentioning
confidence: 99%